Study of working processes of reciprocating compressors of road-building machines - Sergey S. Busarov; Marina A. Rashchupkina; Dmitry R. Marchenko (Вестник СибАДИ)
Introduction. The article presents studies of the possibility of increasing gas pressure in one stage. Reciprocating compressors of road construction machines have been investigated, for which, as for any mobile stations, the issue of reducing the weight and size parameters of process equipment is acute. In this regard, the aim of the work was to expand the range of pressures obtained in single-stage piston machines. An alternative to the use of existing compressors with lubricated flow part can be compressors with seals based on fluoroplastic compounds that do not require liquid lubrication. In this regard, an urgent task is to determine the range of pressure ratios with a limitation on the operating temperature of non-lubricated seals. The increase of the pressure in one compression stage will significantly improve the efficiency of mobile compressor units, including applied for road construction works.Materials and methods. Based on the developed mathematical model of concentrated gas parameters, theoretical studies were carried out to determine the temperature of the cylinder-piston seals of the compressor. The article presents simplifying assumptions adopted in the mathematical model and a system of calculation equations, the main among which are the equation of the first law of thermodynamics, the equation of state, the equation of work and the equation for calculating mass flows through leaks in the working chamber and valves.Results. The diagrams of average temperature change for single-stage machines and for the case of short-term compressor operation were obtained on the basis of theoretical studies. The temperature limit has been set at+200 0С, which is typical for the studied fluoroplastic-based materials.Discussion and conclusions. Promising results were obtained that showed the possibility of expanding the pressure range in a single-stage machine. In cases where strict conditions for gas temperature are not required, the pressure ratio in such compressors can reach 16. In this case, the receiver volume can be reduced to 44%. The option with short-term compressor operation from 15 to 45 minutes has also studied, where the range of the pressure ratio can be increased to 28 ... 30, but the compressor cooling time must not be less than 1 hour.